Role of laparoscopic cholecystectomy in the management of chronic right upper quadrant pain due to biliary dyskinesia: a systematic review and meta-analysis - Rehman, Saad; Singh, Krishna Kumar; Sajid, Muhammad Shafique (Translational Gastroenterology and Hepatology; Vol 4 (September 2019): Translational Gastroenterology and Hepatology, 2019)
Background: The objective of this study was to evaluate the surgical outcomes and feasibility of performing laparoscopic cholecystectomy (LC) in patients with longstanding right upper quadrant pain secondary to biliary dyskinesia. Methods: A systematic review of the literature including published randomized, controlled trials, non-randomized trials and comparative trials of any type, reporting outcomes of LC in the management of chronic right upper quadrant pain in patients with biliary dyskinesia, using the principles of meta-analysis on RevMan 5.3 statistical software, was undertaken. Results: Thirteen studies including 740 patients evaluating the symptomatic improvement following LC in patients with biliary dyskinesia presenting as chronic right upper quadrant pain were included. There were 542 patients in LC group and 198 patients in Non-LC group. Successful complete resolution of symptoms was more likely to be achieved in LC group [risk ratio (RR), 0.21; 95% confidence interval (CI), 0.09–0.50, P=0.0005]. In addition, the risk of failure to resolve symptoms (risk ratio, 0.15; 95% CI, 0.05–0.39, P=0.0001) was lower in LC group. Conclusions: LC may be considered as an acceptable surgical intervention in patients with biliary dyskinesia presenting with chronic right upper quadrant pain. Currently there is insufficient evidence to recommend the routine use of LC in every patient with biliary dyskinesia. Paucity of high power randomised, controlled trials is the major reason for this lack of evidence which should be addressed soon and until then current study may be used to provide the basis for offering LC in selected group of patients.